Reinhart Ahlrichs (1940–2016). Issue 1 (16th December 2016) - Gauss, Jürgen; Ochsenfeld, Christian
Abstract : Reinhart Ahlrichs, Professor Emeritus of Theoretical Chemistry at the Karlsruhe Institute of Technology (KIT) and one of the leading figures of both the German and international theoretical chemistry communities, passed away aged 76 on October 12, 2016. His work shaped the field of quantum chemistry and took the interplay between theory and experiment to new levels. He was also the founder of the TURBOMOLE program package.